Sekuritisasi Penanganan Isu Pengungsi di Swedia: Berhasil atau Gagalkah? - Tiffany Setyo Pratiwi Pratiwi (Mediasi: Journal of International Relations, 2019)
ABSTRACT This paper will explain about the securitization process in addressing refugees issue in Sweden from 2010 to 2015. This research uses the concept of securitization from Barry Buzan. Some important things that Buzan explained to analyze the process of securitization, such as: Referent Object (Actors), Existential Threats (things or issues that become threats), then will proceed to be “Securitizing Move” by “Speech Act”. This paper uses qualitative method which is arranged descriptively with support by secondary data. This paper found that the process of securitization on refugee policies in Sweden from 2010 to 2015 is supported by Sweden Democrats Party and gained the response of Swedish anti-immigrant society, they are conducting the “Speech Act” sustainably.  The result is that Sweden's open policy on refugees has changes by restricting and tightening the refugees policy. Keywords: Securitization Process, Democrats Sweden Party, Refugees Issue, Swedish Government, Swedish Society Response